Affection of academic performance by lifestyles in nursing students (Horizontes de Enfermería, 2019)
Human beings have been creating and adapting certain behaviors and habits, which can be modified throughout their lives, helping them to face different scenarios in their daily lives or society where they operate. To evaluate the Nursing student lifestyles of the Universidad Politécnica Estatal del Carchi and compare if they affect their academic performance. Descriptive, quantitative, non-experimental, cross-sectional and correlational study applied to 70 fourth semester undergraduate students of the Nursing at the Universidad Politécnica Estatal del Carchi. The data were processed in the SPSS program with a powerof 80%, with an average of 1.8 and a standard deviation (SD) of 6.9, frequencies, ANOVA. The average age among participants is 18-20 years. This research determined that students spend more than two hours studying; their academic performance is between good and very good, which they said that it had decreased due to spending a lot of time on social networks; sometimes they do not attend classes due to illness, laziness, or fall asleep; they almost never drink alcohol; Sometimes they do physical sports; they read little, which greatly affects their academic performance and their diet is unhealthy. Unhealthy lifestyles were evidenced in most of the dimensions evaluated in nursing students. It is suggested to propose strategies topromote activities to achieve greater use of free time and motivate physical activity.
Keywords: Lifestyles; academic performance; quality of life